If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9u + -38 = 4(u + 3) Reorder the terms: -38 + 9u = 4(u + 3) Reorder the terms: -38 + 9u = 4(3 + u) -38 + 9u = (3 * 4 + u * 4) -38 + 9u = (12 + 4u) Solving -38 + 9u = 12 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. -38 + 9u + -4u = 12 + 4u + -4u Combine like terms: 9u + -4u = 5u -38 + 5u = 12 + 4u + -4u Combine like terms: 4u + -4u = 0 -38 + 5u = 12 + 0 -38 + 5u = 12 Add '38' to each side of the equation. -38 + 38 + 5u = 12 + 38 Combine like terms: -38 + 38 = 0 0 + 5u = 12 + 38 5u = 12 + 38 Combine like terms: 12 + 38 = 50 5u = 50 Divide each side by '5'. u = 10 Simplifying u = 10
| 13x^2-120x+201=0 | | (-a^2+3)-(a^2-1)+(4a^2-5a+6)= | | 2x-x=108 | | .20(y-7)+.06y=.18y-.03(30) | | x^2-50x-600=0 | | 0.4x^4-1.6x-1=0 | | (2n+3m)+(5n+8m)= | | 2log(x)-log(7x)=1 | | 25(x-4)=-55(x-10) | | h=-16t^2+8t+4 | | 35X^2+51X-8= | | 0=3log(2-h) | | 3m(6m+18)= | | -4.9t^2+21t+120=0 | | 2(3-1)= | | -12x^2+4x=0 | | y=-0.571428571429x+0.428571428571 | | 15x+6-12x+8=10 | | ln(7x-1)=-2 | | =202a+6 | | ln(x^2-2)=5 | | 2.3*-4+1.2x=3.5 | | 2x-1=5x+7 | | 8-6p+24=7p+23 | | 40-3x=12-7x | | (7x)+(-3x)= | | (-2y)+(-3)= | | 0=2*x*cos(x)-x | | 3(3y+1)=85 | | 4x+16=21-x | | x+31=3x+15 | | 2.5-3.5x=-32x-48 |